(untitled) (Costos y Gestión, 2021)
The present research addresses the issue of analyzing institutional aspects of livestock in the southwest of Buenos Aires Province as an interorganizational network by identifying relevant actors of the organizational field, and the type of links they maintain, while considering the degree of concentration within the primary links and industry where the economic power of small and medium producers is observed. Likewise, this work seeks to understand the dynamics of the transactions carried out by the actors within the chain by determining the dimensions which characterize them, and the governance mechanisms that emerge from them. In this way, the aim is to complement the approaches traditionally applied to the study of agribusiness in order to consider other actors and links based on normative, cultural or cognitive aspects, which condition the behavior of agents. Initially, a mapping of the organizational field is carried out which manifests its complexity because of the diversity of actors involved and the type of relations they maintain with each other. The configuration of the inter-organizational networks that make up the field presents certain stability in the links, which would favor a rapid diffusion of information and knowledge if the number of ties between the agents was increased. This stage identifies the most relevant actors within each link in the chain, which are considered to analyze pressure from the institutions and factors that influence the coordination or governance mechanisms that the chain adopts. As regards the pressure from institutions affecting agribusiness, they are mostly of coercive and normative origin – the former as a consequence of dependency of access to critical resources, and the latter from the action of professional advisers. As regards the governance of the chain, a modality through the market is inferred, with a tendency towards a modular or even relational structure, as a result of the demands of the international market. This work enriches the academic-scientific field by providing a conceptual framework that integrates the theoretical approaches belonging to the administration field, which are generally independently applied on the study of agribusiness, from a perspective of complementarity.